Outcome of Febuxostat treatment in hyperuricemic pre-dialysis chronic kidney disease patients - Shrestha, Dineshowri; Baral, Anil; Dahal, Kashyap; Shrestha, Juju Raj; Hada, Rajani (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Hyperuricemia is a cause and effect of chronic kidney disease (CKD), accelerates its progression and predisposes to acute kidney injury. Present study aimed to find out the outcome of Febuxostat treatment in hyperuricemic pre-dialysis CKD patients.Method: This was a cross sectional study conducted in Nephrology department, Bir hospital, Nepal, during from February 2019 to January 2020, among pre-dialysis CKD stage 3-5 non dialysis (ND) patients with serum uric acid (SUA) >7 mg/d L who were treated with Febuxostat 40 mg once a day and followed up at one, two and three months. The baseline SUA, creatinine, estimated glomerular filtration rate (eGFR) calculated by the modification of diet in renal disease (MDRD) equation compared with values at follow up and according to CKD stages. The adverse effects and liver enzymes were recorded.Result: There were total 50 patients, mean age 54.2±16.5 years, male 31 (62%).There were significant reductions of SUA from baseline of 8.9±1.4to 7.1±1.2 vs 5.9±0.9 vs 4.7±1.0) at one, two and three month respectively, p=0.000 and increment of eGFR (ml/min/1.73m2) from 29.6±15.0 to 31.6±16.0, 33.6±16.6, 34.1±17.1, p=0.000.And 41 (82%) patients achieved uric acid < 6 mg/dl at three month. Significant reduction of uric acid in all CKD stages and increment of eGFR in CKD stage 3 and 4 were observed. Adverse effects were epigastralgia in 5 (10%) and joint pain in 13 (26%).Conclusion: Febuxostat is an effective serum uric acid lowering drug in pre-dialysis chronic kidney disease patients with improvement of kidney function.